Evaluation of seasonal changes of triterpenic acid contents in Viscum album from different host trees. (1st January 2017) - Wójciak-Kosior, Magdalena; Sowa, Ireneusz; Pucek, Kamila; Szymczak, Grażyna; Kocjan, Ryszard; Luchowski, Piotr
Abstract: Context: Viscum album L. (Loranthaceae) is a semi-parasitic plant used in pharmacy and medicine mostly for its hypotensive and anticancer activity. The effects may be related to the presence of triterpenic acids, such as betulinic (BA) and oleanolic (OA) acids. Objectives: In our investigations the content of triterpenic acids in V. album from different host trees depending on the season of harvest was determined. Material and methods: V. album herb was dried and extracted with ethyl acetate using ultrasound energy. The reversed phase HPLC-PDA method was used for the analysis of triterpenic acids. The structure of the target components was confirmed by mass spectrometry with an electrospray ionization source. Results: Diversity in the content of both compounds was noted; however, OA was the dominant triterpenic acid and the amount thereof was ∼10 times higher than that of BA. The analysis of changes in the amount of triterpenic acids during the spring-winter period revealed the highest content of OA in summer (from 6.84 to 13.65 mg/g). In turn, in the other seasons of harvest, the content was in the range of 4.41–9.83, 6.41–9.56 and 5.59–12.16 mg/g for spring, autumn and winter, respectively. In most cases, a similar tendency was observed for BA. Discussion and conclusion: In most cases, the highest amount of the investigated compounds was found in summer; thus, this period seems to be optimal for acquisition of plant material rich in triterpenic acids.